Reception Analysis of Halal Food among the Online Platform Audiences in Muslim Minority Countries - Sari, Adinda Permata; Dwijayanti, Risqi Inayah; Sarasati, Fitri; Marta, Rustono Farady; Lumampauw, Andreas (State Islamic Institute of Bone, Indonesia, 2024)
Halal Lifestyle is a fundamental aspect of the Muslim community's lifestyle, as consuming halal products is a religious obligation and necessity for Muslims. However, this is a significant challenge in Muslim minority countries due to limited access to halal cuisines in public places. This research aims to understand the process of audience acceptance in countries with minority Muslims regarding the need for consumption following halal principles. Researchers employ audience acceptance theory in analyzing research problems and an analysis technique coined by Stuart Hall. The data was obtained through the use of research instruments in the form of guided discussions, based on the constructivist paradigm through the employment of data reduction, data presentation, and validation process. The results of the guided discussions indicated that each participant interpreted media messages in three possible positions: dominant, negotiation, and opposition. These differences in interpretation were influenced by various individual backgrounds, including where they lived, their views, and their experiences. The findings indicate that, in terms of acceptance of halal food in Muslim-minority countries, the majority of participants consider information about halal food to be important in maintaining their religious beliefs, particularly through online platforms such as websites and Instagram.